Pengaruh Terapi Komplementer Lavender Inhaler Stick Untuk Mengurangi Mual Muntah Pada Ibu Hamil Trimester 1 - Pertiwi, Desi; Mayangsari, Rr. Nindya; Noorbaya, Siti (CV. Utility Project Solution, 2023)
Nausea and vomiting is a common discomfort experienced by 50-90% of pregnant women, generally occurring in the first trimester. One of the treatments to reduce non-pharmacological therapy is giving lavender aromatherapy. The aim of this study was to determine the effect of giving lavender inhaler stick to reduce vomiting and nausea in first trimester pregnant women. The research method used was a quasy experiment with a pretest-posttest approach with a control group design. The sampling technique used was quota sampling, a sample of 30 first trimester pregnant women in the Sempaja Health Center area was divided into a control group and an experimental group. This study shows that there is an effect of giving lavender inhaler stick to reduce vomiting and nausea in first trimester pregnant women in the Sempaja Health Center area. Giving lavender inhaler stick is good for reducing nausea and vomiting for pregnant women because it will affect the nerves in the hypothalamus to reduce nausea and vomiting.